Exploring Geometric Chirality in Nanocrystals for Boosting Solar‐to‐Hydrogen Conversion - Fu, Wenlong; Gao, Qi; Zhang, Chunyang; Tan, Lili; Jiang, Biao; Xiao, Chengyu; Liu, Maochang; Wang, Peng‐peng (Angewandte Chemie International Edition, 2024)
Advancing catalyst design is pivotal for the enhancement of photocatalytic processes in renewable energy conversion. The incorporation of structural chirality into conventional inorganic solar hydrogen nanocatalysts promises a significant transformation in catalysis, a feature absent in this field. Here we unveil the unexplored potential of geometric chirality by creating a chiral composite that integrates geometric chiral Au nanoparticles (NPs) with two‐dimensional C3N4 nanosheets, significantly boosting photocatalytic H2 evolution beyond the achiral counterparts. The superior performance is driven by the geometric chirality of Au NPs, which facilitates efficient charge carrier separation through the favorable C3N4‐chiral Au NP interface and chiral induced spin polarization, and exploits high‐activity facets within the concave surfaces of chiral Au NPs. The resulting synergistic effect leads to a remarkable increase in photocatalytic H2 evolution, with an apparent quantum yield of 44.64 % at 400 nm. Furthermore, we explore the selective polarized photo‐induced carrier separation behavior, revealing a distinct chiral‐dependent photocatalytic HER performance. Our work advances the design and utilization of chiral inorganic nanostructures for superior performance in energy conversion processes. The potential of geometric chiral effect was explored to enhance photocatalytic H2 evolution using a chiral composite of geometric chiral Au nanoparticles (NPs) and C3N4 nanosheets. The chiral Au NPs enable efficient charge carrier separation and high‐activity facets, boosting performance over achiral counterparts and resulting in a quantum yield of 44.64 % at 400 nm. Chiral‐dependent photocatalytic performance was also revealed.